MANAJEMEN RISIKO KREDIT DAN LIKUIDITAS PADA BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH PERIODE JUNI 2019 – MEI 2020 - Clara Debiora Leviana Rumere; Lis Sintha Oppusunggu (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The purpose of this study is to get an overview of risk management in the dual banking system, namely Conventional Commercial Banks and Islamic Commercial Banks in Indonesia. In this case, risk management focuses on credit or financing risk and liquidity risk. The data source used in this research is secondary data. While the data collection techniques used in this study are in the form of literature and documentation. The sample of this research is in the form of financial reports on Conventional Commercial Banks and Islamic Commercial Banks for the June 2019-2020 period. For data analysis techniques, the study used the Independent Sample t-test. The results of the research show that in credit risk management a. From the perspective of a significant value of 0.00, it means lower than the research alpha (0.05). If the significant value (2 tailed) < alpha research (0.05), then the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This means that there is a difference in credit risk between conventional banks and Islamic banks. b. From the perspective of the t value of 3,997, it means that it is greater than the t table of 2,179. If the t-count value > t-table, then H0 is rejected and Ha is accepted. This means that there is a difference in credit risk between conventional banks and Islamic banks. While on liquidity risk management a. From the perspective of a significant value of 0.00, it means lower than the research alpha (0.05). If the significant value (2 tailed) < alpha research (0.05), then the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This means that there are differences in liquidity risk between conventional banks and Islamic banks. b. From the perspective of the t value of 6,747, it means that it is greater than the t table of 2,179. If the t-count value > t-table, then H0 is rejected and Ha is accepted. This means that there are differences in liquidity risk between conventional banks and Islamic banks.